Preservice Middle School Mathematics Teachers’ Development in Formative Assessment - Gözde Can; Çiğdem Haser (Netherlands, 2022)
The study was conducted to investigate preservice middle school mathematics teachers’ professional development in formative assessment practices they plan to implement in classrooms. Basic qualitative research method was employed in this study. Incomplete and Improper Lesson Plan Task developed by the researchers was implemented to 47 2nd year, 37 3rd year, and 27 4th year preservice middle school mathematics teachers. Findings of the study indicated that participants who took measurement and assessment course and methods of teaching courses (3rd year and 4th year preservice teachers) emphasized integrating formative assessment strategies more than 2nd year preservice teachers. None of the participants mentioned to give opportunity to students to assess themselves or provide feedback to the students in order to enhance their learning. 3rd year and 4th year preservice teachers were also more successful in detecting the improperness of the lesson plan.
Proceedings of the Eleventh Congress of the European Society for Research in Mathematics Education